Oxidant-free oxidative gold catalysis: the new paradigm in cross-coupling reactions - Akram, Manjur O.; Banerjee, Somsuvra; Saswade, Sagar S.; Bedi, Vaibhav; Patil, Nitin T. (Chemical Communications, 2018)
The construction of C-C and C-X (X = hetero atom) bonds is the core aspect for the assembly of molecules. In this regard, late transition-metal-catalyzed cross-coupling reactions have retained their dominance for decades. Lately, gold catalysts have been emerging as a reliable contender for such transformations owing to the recent findings that reveal gold's potential beyond carbophilic -Lewis acid. The newfound ability of gold to undergo redox transformations under certain circumstances has allowed us to explore gold catalysts as a viable alternative to other late transition-metals for efficient construction of cross-coupled products. This feature article critically presents an overview of all the redox neutral cross-coupling reactions enabled by gold catalysis, which we believe would stimulate further research activities in this promising area.